2020
DOI: 10.3390/jpm10010007
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Utilization and Costs after Receiving a Positive BRCA1/2 Result from a Genomic Screening Program

Abstract: Population genomic screening has been demonstrated to detect at-risk individuals who would not be clinically identified otherwise. However, there are concerns about the increased utilization of unnecessary services and the associated increase in costs. The objectives of this study are twofold: (1) determine whether there is a difference in healthcare utilization and costs following disclosure of a pathogenic/likely pathogenic (P/LP) BRCA1/2 variant via a genomic screening program, and (2) measure the post-disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 32 publications
4
31
0
Order By: Relevance
“…Among 147 women with at least 1 P/LP variant in the 7 breast cancer susceptibility genes, 56 (0.38%, 95% CI = 0.30% to 0.46%) unselected individuals had BRCA1/2 P/LP variants. This prevalence of 0.38% is consistent with the 0.2%-0.7% prevalence of BRCA1/2 P/LP variants reported in previous studies ( 9 , 15 , 30 , 31 ). The frequency of BRCA1/2 P/LP variants differs across race and ethnicity: 41.7% in the 108 European-ancestry individuals, 30.4% in the 23 African Americans, 15.4% in the 13 Latina, and 50.0% in the 4 Asians.…”
Section: Resultssupporting
confidence: 92%
“…Among 147 women with at least 1 P/LP variant in the 7 breast cancer susceptibility genes, 56 (0.38%, 95% CI = 0.30% to 0.46%) unselected individuals had BRCA1/2 P/LP variants. This prevalence of 0.38% is consistent with the 0.2%-0.7% prevalence of BRCA1/2 P/LP variants reported in previous studies ( 9 , 15 , 30 , 31 ). The frequency of BRCA1/2 P/LP variants differs across race and ethnicity: 41.7% in the 108 European-ancestry individuals, 30.4% in the 23 African Americans, 15.4% in the 13 Latina, and 50.0% in the 4 Asians.…”
Section: Resultssupporting
confidence: 92%
“…The PROSE consortium findings were supported by a small sample of RRM and RRSO uptake data from the Geisinger MyCode Community Health Initiative, which found that the RRM uptake during the first year of follow-up was 3.5% (2 of 57) and that the RRSO uptake was 11.8% (6 of 51) among known pathogenic BRCA1/2 carriers. 33 We did not identify comparable prophylactic surgery uptake data for non- BRCA1/2 variants, so we assumed RRM and RRSO uptake rates of 50% of the averaged uptakes of BRCA1 and BRCA2 carriers.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, EHR access also enables correlation of clinically relevant results with personal and family history of disease leading to more informed clinical care. Lastly, implementation of population genomic screening in an integrated, learning healthcare system allows longitudinal analyses of outcomes data and can inform future guidance on the personal, medical, and financial utility of such programs (Buchanan et al, 2020; Haggerty et al, 2017; Hao et al, 2020; Jones et al, 2018; Patel et al, 2019; Savatt et al, 2020) and facilitate expansion beyond what most programs are reporting at this time (Martin et al, 2020; Savatt et al, 2020).…”
Section: Challenges and Benefits Encounteredmentioning
confidence: 99%
“…While population‐scale genomic screening poses new challenges compared to current patient‐level approaches in the diagnostic setting, much of the literature on population‐scale screening has focused on recruitment, consent, clinical utility, and results disclosure (Buchanan et al, 2020; Grzymski et al, 2020; Hao et al, 2020; Ilori et al, 2020; Murray et al, 2018; Schwartz et al, 2018). Little attention has been given to the operational challenges of evaluating genomic data at a population‐scale.…”
Section: Introductionmentioning
confidence: 99%